A Study of Dakwah Pattern on Dramatic Text and Its Transformation From Serat Menak Lare Literature to the Choreography Text of Srimpi Dance - Pramutomo, R.M.; Widyastutieningrum, Sri Rochana; Kuncoro, Jonet Sri (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2020)
The Srimpi dance is a Javanese dance which is presented by four female dancers. Usually, the Srimpi dancers are four female teenagers. The dance itself is based on literature. On the Srimpi Menak lare variation, the dance is performed by four child dancers, specifically by two boys and two girls. The Srimpi Menak Lare dance was inspired from the childhood tale of Tiyang Agung Jayengrana or Amir Ambyah, one of the uncles of Prophet Muhammad on a play by R.Ng. Yosodipuro I. The dramatical transformation in said play, when choreographically visualized, becomes a topic of discussion. This article will examines a study of dance elements which is pattered by da’wah in Islamic point of view. Based on said discussion, the creation of Srimpi Menak Lare dance is a research-based dance creation from the idea forming, exploration, concept building, and the forming of the dance itself. The methodological application in this artistic research refers to the analitycal form of the innovative choreography of the Srimpi Menak Lare dance. Through this specific term of da’wah pattern this article applied an exploration of elements of dance creation related to the contens of da’wah in Islamic values.